Ethos en el liderazgo de los gestores de talento humano de las universidades y escuelas politécnicas del Distrito Metropolitano de Quito (Estudios) - Logaña Guallichico, Hilda Esperanza (2020)
Ethos in leadership is the ontological foundation (existing-real-philosophical) of a profession and dictates, marks, guides the disposition of the Manager when exercising the functions that by his profession performs, as well as determines how to achieve professional fulfilment. Ethos cannot be treated individually but as a result of: a particular social structure, politics, economics and even culture; Ethos’ reference is dynamic because it is changeable over time, modifiable and turns out to be part of both personal and social trajectory. Among the personal factors that affect Ethos are: age, income, type of education, job stability, health aspects and social factors including public and private systems. This study shows from the bibliography a theoretical foundation of all the elements, concepts, the moral-professional being, the motivational structure, the context of ethics, leadership, and the formation of the Human Talent Manager. The analysis of the Ecuadorian and South American university is contextualized, within the framework of the reforms that have taken place in the universities and the competitiveness strategies among them.